Electric Field Controlled Anisotropic Rashba Splitting in Janus Chromium Dichalcogenide Monolayers : A Computational Study based on Density Functional Theory - Muhammad Anshory; Yusron Darojat; Yusuf Affandi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
In this study, we explore the electronic structure of Janus Chromium Dichalcogenide monolayers CrXY (X ? Y = S, Se, Te) in the first Brillouin zone using Density Functional Theory. Due to the mirror symmetry break and strong SOC in the crystal structure of Janus Chromium Dichalcogenide monolayer, we discovered Rashba splitting at ? points in the first Brillouin zone. We analyze this anisotropy of Rashba splitting using k?p perturbation theory and group symmetry analysis. By giving the effect of external electric field, we manipulate the characteristics of Rashba splitting on the Janus Chromium Dichalcogenide monolayer. The manipulation of Rashba splitting by applying external electric field, shows that the Janus Chromium Dichalcogenide monolayers has the potential for spintronic devices.